تقدير للعوامل السياسية والاقتصادية المؤثرة على الفساد في الجزائر في الفترة 2003-2020 - بوعافية, هشام (جامعة الوادي University of Eloued, 2021)
تهدف هذه الدراسة إلى تحليل العوامل والأسباب المشجعة لبروز ظاهرة الفساد بمختلف أشكالها ومظاهرها (الفساد الإقتصادي والمالي والسياسي) وهذا من أجل معرفة أهم الاستراتيجيات المتبعة لمكافحتها. وذلك من خلال أخذ مجموعة من المؤشرات السياسية والاقتصادية في تقييم درجة الفساد، حيث تم قياس درجة الفساد من خلال مؤشر مدركات الفساد. ومن النتائج المتوصل إليها أن مؤشر الديمقراطية الاجمالي ومؤشر مستوى المشاركة السياسية هما الأكثر تأثيراً في العامل السياسي للفساد في الجزائر، كما توصلت الدراسة أيضا أن مؤشر درجة الحرية الاقتصادية ومؤشر درجة حرية الاستثمار هما الأكثر تأثيراً في العامل الاقتصادي للفساد في الجزائر، كما هنالك علاقة طردية بين العامل السياسي والاقتصادي بمؤشر مدركات الفساد، حيث كلما كان هنالك مناخ سياسي واقتصادي يحارب ظاهرة الرشوة، المحسوبية، نهب والاختلاس واهدار لمال العام. كلما أدى إلى انخفاض ظاهرة الفساد. The aims of this study is to analyze the factors and reasons for the emergence of the phenomenon of corruption in all its forms(economic, financial and political corruption) , in order to know the most important strategies used to combat it, by taking groups of political and economic indicators in assessing the degree of corruption, The degree of corruption was measured through the Corruption Perceptions Index. The results of This study, that the democracy index and the level of political participation index are the most influential in the political factor of corruption in Algeria. This study also found that the degree of economic freedom index and the degree of investment freedom index are the most influential in the economic factor of corruption in Algeria.
An estimate of the political and economic factors affecting corruption in Algeria in the period 2003-2020
مقال
Keywords: الفساد ; مؤشر مدركات الفساد ; الفساد الاداري ; الفساد الاقتصادي ; البيروقراطية